Transient Analysis of Single Machine Production Line Dynamics - Rismanchian, Farhood (Eastern Mediterranean University (EMU), 2013)
ABSTRACT: In this thesis a single machine production line is modeled by an alternating renewal process. We derive efficient approximations for the first and second order transient performance measures of a production line which can be in one of the two states up(working) or down(failed), modeling the production line by an alternating renewal process. A due date performance measure is derived and discussed. The thesis also discusses two optimizations problems in the production line. Numerical examples are provided to illustrate the procedure. Keywords: production line, alternating renewal process, renewal function, availability function, due date performance. ………………………………………………………………………………………………………… ÖZ: Bu tezde almaşık yenileme süreci ile tek makinalı bir üretim hattı modellenmiştir. Durumu yukarıda(çalışan) veya aşağıda(başarısız) olabilen bir üretim hattı’nın birinci ve ikinci derece geçici başarım ölçütlerine verimli yaklaşıklama türetiyoruz. Bu üretim hattı almaşik yenileme süreci ile modellenmiştir. Ayrıca bir vade tarihi başarim ölçütü türetilmiş ve tartışılmıştır. Bu tez ayni zamanda üretim hattinda iki eniyileme problemi irdelemektedir. Prosedürü göstemek için sayısal örnekler sağlanmiştir. Anahtar kelimeler: üretim hatti, almaşik yenileme süreci, yenileme fonksiyonu, vade tarihi başarımı.
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2013. Supervisor: Prof. Dr. Alagar Rangan.
Keywords: Industrial Engineering; Production Management - Production Line; Production Line - Alternating Renewal Process - Renewal Function - Availability Function - Due Date Performance